Lahauli verb inflection - Singh, J. D. (2024)
Lahauli is a language of the Tibeto-Burman family spoken on the northwestern border of India, in the Districts of Lahaul and Spiti in the Himachal Pradesh. Lahauli has several dialects; the variety chosen for study here is spoken in Nalda village, Post Office Muring and Tahsil Keylong. The informant, Shri Durga Das s/o Shri Lal Das, comes from a high caste and is a native speaker of the dialect; in addition, he knows Hindi and English.